BOOK REVIEW OF ANGELA’S ASHES NOVEL BY FRANK MC COURT - Wibowo, Bimoseno Budi (LANTERN (Journal on English Language, Culture and Literature), 2016)
This book review is written to find the strength and the weakness in Angela’s Ashes which iswritten by Frank Mc Court. “The Book Review of Angela’s Ashes” is focusing on the content ofthe novel finding the strength and the weakness. The strengths are theme, character setting, and moral value, the weakness is the end of the story. The plot conveys how the author describes allsituations in this novel clearly and the main character shares readers about how to face the worldand he shares lot of values in his life as poor boy. The weakness is the end of the story. Mc Courtdoes not give explanation about how is the novel continuity. This novel conveys about how to bea person that always keeping strong for this life and there are so many moral values in this novel.